Dealing with financial fragility in transition economies - John Bonin; Paul Wachtel (Bank of Finland, Institute for Economies in Transition (BOFIT), 2004)
We examine the efforts of transition economies to deal with financial fragility and resolve banking cries We characterize the birthing process of banking in transition and the three essential features of banking crises in transition economies: (i) bad loans and the relationship to state owned industries, (ii) development of institutional infrastructure and (iii) credible commitments to resolution and privatization.We then discuss the experiences of seven important transition countries in order to identify the salient features of their efforts to resolve banking crises.
URN:NBN:fi:bof-201408071964
Keywords: 330